Complication and revision rate in complex intraarticular calcaneal fractures: extended lateral vs sinus tarsi approach - Barbari, Jan el; Meyer, Matthias; Grützner, Paul Alfred; Swartman, Benedict; Vetter, Sven Y.; Franke, Jochen (Foot & ankle international, 2025)
Background: Adequate surgical treatment of intra-articular calcaneal fractures is challenging. Current clinical evidence on the superiority of either the extended lateral approach (ELA) or the sinus tarsi approach (STA) and their impact on radiologic and functional outcome remains inconclusive, and studies are characterized by low case numbers and short follow-up periods. We hypothesized that using STA would lead to fewer complications and revisions, without impairing fracture reduction or short- to midterm outcome. - Methods: This retrospective cohort study included 241 patients with intra-articular calcaneal fractures receiving surgical therapy by ELA or STA from 2014 to 2020. A propensity score matching was performed to adjust for covariates distribution after which 140 complete data sets were available for analysis. The primary endpoint was the time to surgical revision. Secondary endpoints were time to complication, complication, as well as revision rate, operating room time, length of stay, and the radiologic and functional outcome (12-Item Short Form Health Survey [SF-12], Visual Analogue Scale for Foot and Ankle [VAS-FA]). - Results: The hazard ratio for surgical revision was 1.74 (95% CI 0.82-3.68) and for complications 1.66 (95% CI 0.82-3.33), both indicating no difference. Radiologic outcome, assessed by remaining step (P = .437) and gap (P = .911) and the reduction grading (P = .564), as well as the functional outcome assessed by the SF-12 (P = .827) and the VAS-FA (P = .930) was comparable in both groups. - Conclusion: Compared with conventional ELA, the less invasive surgical technique via STA has similar short- to midterm complications and is associated with comparable anatomical reductions and functional outcomes. The propensity matching of the fracture severity gives us confidence to consider STA a suitable surgical approach in moderate and severe Sanders 3 and 4 type fractures.
Online veröffentlicht: 12. März 2025
Gesehen am 07.08.2025